Avaliação ultraestrutural e funcional do espermatozoide humano submetido ao processo de liofilização - Marcelo Araujo Cabral (2017)
Introduction - In recent years the conservation of semen has become expensive and difficult. Sperm banks are fundamental to promote in special situations the possibility of reproduction of couples with reproductive difficulties. The cost is determined by the need for the use of liquid nitrogen, physical area and permanent surveillance of the process by specialized personnel. The alternative that is sought in this situation is a more practical and low cost. Freeze Dried is a process which is based on the withdrawal of liquid from any biological or not structure. It is widely used in the drug and food industry. The possibility of preservation of human sperm after Freeze Dried is one of the ways that aims to reduce costs in the storage of this reproductive cell. Purpose - To analyse the impact of Freeze Dried on the morphological and functional structure (DNA integrity) of human spermatozoa subjected to cryopreservation and subsequent FreezeDried. Material and Methods - 26 samples of semen supplied by healthy volunteers were used to perform the research. Samples were evaluated by spermogram that revealed normal parameters (WHO). The samples were submitted to cryopreservation and subsequent Freeze Dried in different culture media (FreezingMedium, SpermFreezeSolution, mHTF, Gamete and EDTA solution). After lyophilized and rehydrated spermatozoa were analyzed through scanning electron microscopy (morphological evaluation) and through functional DNA integrity tests (Halosperm and Negrosin eosin test). Results - All the samples analysed, regardless of the culture medium used, showed morphological lesions in their ultrastructure (head, cell membrane, tail). Functional tests revealed significant DNA lesions of the germ cells analyzed. All spermatozoa were inert and with a functional diagnosis of cell death. Discussion - The study revealed that the techniques used for cryopreservation and Freeze Dried used is generating loss of the ultra-structural and functional characteristics of the analyzed spermatozoa. Some technical variations of Freeze Dried should be tested to try to obtain more favorable results than those reached in the present study. Conclusions - Human spermatozoa after being submitted to Freeze Dried showed evident ultra - structural alterations, as well as impairment of their functional capacity to maintain intact nuclear DNA. The observed ultrastructural and functional alterations showed small variations according to the culture medium in which they were subjected to Freeze Dried, indicating the need for new studies related to techniques different from those studied, in the hope of finding a better way of protection for the spermatozoa during the Freeze Dried process.